الحرمان العاطفي وعلاقته بالابتزاز الالكتروني لدى طالبات الدراسة الاعدادية (Journal of the College of Basic Education, 2024)
The current research aimed to identify emotional deprivation among middle school students, and to identify Cyberblackmail among middle school students, and the correlation between emotional deprivation and Cyberblackmail among middle school students. The researchers adopted the Al-Saadi scale (2016) to measure emotional deprivation, consisting of (34) items. Al Samarrai scale (2021) was also adopted to measure Cyberblackmail consisting of (20) items after verifying the validity and reliability of the two scales. The size of the research sample was (200) female students who are present in preparatory schools in Baghdad Al-Karkh Education (first, second, and third), and the results showed the following The research sample did not have emotional deprivation. And that the students were not subjected to Cyberblackmail, and they determined their position positively towards the issue of Cyberblackmail. Emotional deprivation with Cyberblackmail is also associated with a positive relationship, that is, the lower the level of emotional deprivation for the individual, the less Cyberblackmail.